Anxiety symptoms and children's eye gaze during fear learning. (24th July 2017) - Michalska, Kalina J.; Machlin, Laura; Moroney, Elizabeth; Lowet, Daniel S.; Hettema, John M.; Roberson‐Nay, Roxann; Averbeck, Bruno B.; Brotman, Melissa A.; Nelson, Eric E.; Leibenluft, Ellen; Pine, Daniel S.
Abstract : Background: The eye region of the face is particularly relevant for decoding threat‐related signals, such as fear. However, it is unclear if gaze patterns to the eyes can be influenced by fear learning. Previous studies examining gaze patterns in adults find an association between anxiety and eye gaze avoidance, although no studies to date examine how associations between anxiety symptoms and eye‐viewing patterns manifest in children. The current study examined the effects of learning and trait anxiety on eye gaze using a face‐based fear conditioning task developed for use in children. Methods: Participants were 82 youth from a general population sample of twins (aged 9–13 years), exhibiting a range of anxiety symptoms. Participants underwent a fear conditioning paradigm where the conditioned stimuli (CS+) were two neutral faces, one of which was randomly selected to be paired with an aversive scream. Eye tracking, physiological, and subjective data were acquired. Children and parents reported their child's anxiety using the Screen for Child Anxiety Related Emotional Disorders. Results: Conditioning influenced eye gaze patterns in that children looked longer and more frequently to the eye region of the CS+ than CS− face; this effect was present only during fear acquisition, not at baseline or extinction. Furthermore, consistent with past work in adults, anxiety symptoms were associated with eye gaze avoidance. Finally, gaze duration to the eye region mediated the effect of anxious traits on self‐reported fear during acquisition. Conclusions: Anxiety symptoms in children relate to face‐viewing strategies deployed in the context of a fear learning experiment. This relationship may inform attempts to understand the relationship between pediatric anxiety symptoms and learning.